Handbook of Porous Silicon - Canham, Leigh (Springer International Publishing : Imprint: Springer, 2014)
The Handbook of Porous Silicon brings together the expertise of a large, international team of almost 100 academic researchers, engineers, and product developers from industry across electronics, medicine, nutrition and consumer care to summarize the field in its entirity with 150 chapters and 5000 references. The volume presents 5 parts which cover fabrication techniques, material properties, characterization techniques, processing and applications. Much attention was given in the the past to its luminescent properties, but increasingly it is the biodegradability, mechanical, thermal and sensing capabilities that are attracting attention. The volume is divided into focussed data reviews with, wherever possible, quantitative rather than qualitative descriptions of both properties and performance. The book is targeted at undergraduates, postgraduates, and experienced researchers.